Review of Mechanisms and Treatment of Cancer-Induced Cardiac Cachexia - Vignesh Vudatha; Teja Devarakonda; Christopher Liu; Devon C. Freudenberger; Andrea N. Riner; Kelly M. Herremans; Jose G. Trevino (Cells, 2022)
Cancer cachexia is a multifactorial, paraneoplastic syndrome that impacts roughly half of all cancer patients. It can negatively impact patient quality of life and prognosis by causing physical impairment, reducing chemotherapy tolerance, and precluding them as surgical candidates. While there is substantial research on cancer-induced skeletal muscle cachexia, there are comparatively fewer studies and therapies regarding cardiac cachexia in the setting of malignancy. A literature review was performed using the PubMed database to identify original articles pertaining to cancer-induced cardiac cachexia, including its mechanisms and potential therapeutic modalities. Seventy studies were identified by two independent reviewers based on inclusion and exclusion criteria. While there are multiple studies addressing the pathophysiology of cardiac-induced cancer cachexia, there are no studies evaluating therapeutic options in the clinical setting. Many treatment modalities including nutrition, heart failure medication, cancer drugs, exercise, and gene therapy have been explored in in vitro and mice models with varying degrees of success. While these may be beneficial in cancer patients, further prospective studies specifically focusing on the assessment and treatment of the cardiac component of cachexia are needed.